SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Multi‐Species Telemetry Quantifies Current and Future Efficacy of a Remote Marine Protected Area - Morgan E. Gilmour; Kydd Pollock; Josh Adams; Barbara A. Block; Jennifer E. Caselle; Alex Filous; Alan M. Friedlander; Edward T. Game; Elliott L. Hazen; Marie Hill; Nick D. Holmes; Kevin D. Lafferty; et al. (Global Change Biology, 2025)
Large‐scale marine protected areas (LSMPAs; > 1000 km 2 ) provide important refuge for large mobile species, but most do not encompass species' ranges. To better understand current and future LSMPA value, we concurrently tracked nine species (seabirds, cetaceans, pelagic fishes, manta rays, reef sharks) at Palmyra Atoll and Kingman Reef (PKMPA) in the U.S. Pacific Islands Heritage Marine National Monument. PKMPA and the U.S. Exclusive Economic Zone encompassed 39% and 54% of species movements ( n = 83; tracking duration range: 0.5–350 days), respectively. Species distribution models indicated 73% of PKMPA contained highly suitable habitat. Under two projected future scenarios (SSP 1–2.6, “Sustainability”; SSP 3–7.0, “Rocky Road”), strong sea surface temperature gradients initially could cause abrupt oceanic change resulting in predicted habitat loss in 2040–2050, followed by an equilibrium response and regained habitat by 2090–2100. Current and future suitable habitats were available adjacent to PKMPA, suggesting that increased MPA size could enhance protection. Our three‐tiered approach combining animal tracking with publicly available remote sensing data and future projected environmental scenarios could be used to design, study, and monitor protected areas throughout the world. Holistic approaches that encompass diverse species and habitat use can enhance assessments of protected area designs. Animal telemetry and remote sensing may be helpful for ascertaining the extent to which other MPAs protect large mobile species in the future.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Challenging conventional views on the elevational limits of pronghorn habitat - Ellen O. Aikens; Jessica Speiser; Karma Choki; Michele Lovara; Anna Weesies; Jeffrey Tillery; Sean Ryder; Erica Lafferty; Amanda E. Cheeseman; William J. Severud; Hall Sawyer (Ecology, 2024)

Re-assessing the age of the type locality of Nythosaurus larvatus (Therapsida, Cynodontia) and implications on the evolutionary dynamics of cynodonts - J. Benoit; S. Jirah; E.S. Lund; T. Lafferty; V. Buffa; L.A. Norton (Proceedings of the Geologists' Association, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

The chytrid insurance hypothesis: integrating parasitic chytrids into a biodiversity–ecosystem functioning framework for phytoplankton–zooplankton population dynamics - András Abonyi; Johanna Fornberg; Serena Rasconi; Robert Ptacnik; Martin J. Kainz; Kevin D. Lafferty (Oecologia, 2024)
In temperate lakes, eutrophication and warm temperatures can promote cyanobacteria blooms that reduce water quality and impair food-chain support. Although parasitic chytrids of phytoplankton might compete with zooplankton, they also indirectly support zooplankton populations through the “mycoloop”, which helps move energy and essential dietary molecules from inedible phytoplankton to zooplankton. Here, we consider how the mycoloop might fit into the biodiversity–ecosystem functioning (BEF) framework. BEF considers how more diverse communities can benefit ecosystem functions like zooplankton production. Chytrids are themselves part of pelagic food webs and they directly contribute to zooplankton diets through spore production and by increasing host edibility. The additional way that chytrids might support BEF is if they engage in “kill-the-winner” dynamics. In contrast to grazers, which result in “eat-the-edible” dynamics, kill-the-winner dynamics can occur for host-specific infectious diseases that control the abundance of dominant (in this case inedible) hosts and thus limit the competitive exclusion of poorer (in this case edible) competitors. Thus, if phytoplankton diversity provides functions, and chytrids support algal diversity, chytrids could indirectly favour edible phytoplankton. All three mechanisms are linked to diversity and therefore provide some “insurance” for zooplankton production against the impacts of eutrophication and warming. In our perspective piece, we explore evidence for the chytrid insurance hypothesis , identify exceptions and knowledge gaps, and outline future research directions.

Population genomic structure of a widespread, urban‐dwelling mammal: The eastern grey squirrel ( Sciurus carolinensis ) - Nicole A. Fusco; Bradley J. Cosentino; James P. Gibbs; Maximilian L. Allen; Alexander J. Blumenfeld; George H. Boettner; Elizabeth J. Carlen; Merri Collins; Catherine Dennison; Devin DiGiacopo; André‐Philippe Drapeau Picard; Jonathan Edmonson; et al. (Molecular Ecology, 2024)
Urbanization is a persistent and widespread driver of global environmental change, potentially shaping evolutionary processes due to genetic drift and reduced gene flow in cities induced by habitat fragmentation and small population sizes. We tested this prediction for the eastern grey squirrel ( Sciurus carolinensis ), a common and conspicuous forest‐dwelling rodent, by obtaining 44K SNPs using reduced representation sequencing (ddRAD) for 403 individuals sampled across the species' native range in eastern North America. We observed moderate levels of genetic diversity, low levels of inbreeding, and only a modest signal of isolation‐by‐distance. Clustering and migration analyses show that estimated levels of migration and genetic connectivity were higher than expected across cities and forested areas, specifically within the eastern portion of the species' range dominated by urbanization, and genetic connectivity was less than expected within the western range where the landscape is fragmented by agriculture. Landscape genetic methods revealed greater gene flow among individual squirrels in forested regions, which likely provide abundant food and shelter for squirrels. Although gene flow appears to be higher in areas with more tree cover, only slight discontinuities in gene flow suggest eastern grey squirrels have maintained connected populations across urban areas in all but the most heavily fragmented agricultural landscapes. Our results suggest urbanization shapes biological evolution in wildlife species depending strongly on the composition and habitability of the landscape matrix surrounding urban areas.

A target-cell limited model can reproduce influenza infection dynamics in hosts with differing immune responses - Rahil Sachak-Patwa; Erin I. Lafferty; Claude J. Schmit; Robin N. Thompson; Helen M. Byrne (Journal of Theoretical Biology, 2023)

Mammalian functional diversity and trait responses to anthropogenic and environmental factors across the contiguous USA - Christine C. Rega-Brodsky; Katherine C. B. Weiss; Austin M. Green; Fabiola Iannarilli; Jacquelyn Tleimat; Sarah Fritts; Daniel J. Herrera; M. Caitlin Fisher-Reid; Justin A. Compton; Diana J. R. Lafferty; Maximilian L. Allen (Urban Ecosystems, 2023)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Transient disease dynamics across ecological scales - Yun Tao; Jessica L. Hite; Kevin D. Lafferty; David J. D. Earn; Nita Bharti (Theoretical Ecology, 2021)
Analyses of transient dynamics are critical to understanding infectious disease transmission and persistence. Identifying and predicting transients across scales, from within-host to community-level patterns, plays an important role in combating ongoing epidemics and mitigating the risk of future outbreaks. Moreover, greater emphases on non-asymptotic processes will enable timely evaluations of wildlife and human diseases and lead to improved surveillance efforts, preventive responses, and intervention strategies. Here, we explore the contributions of transient analyses in recent models spanning the fields of epidemiology, movement ecology, and parasitology. In addition to their roles in predicting epidemic patterns and endemic outbreaks, we explore transients in the contexts of pathogen transmission, resistance, and avoidance at various scales of the ecological hierarchy. Examples illustrate how (i) transient movement dynamics at the individual host level can modify opportunities for transmission events over time; (ii) within-host energetic processes often lead to transient dynamics in immunity, pathogen load, and transmission potential; (iii) transient connectivity between discrete populations in response to environmental factors and outbreak dynamics can affect disease spread across spatial networks; and (iv) increasing species richness in a community can provide transient protection to individuals against infection. Ultimately, we suggest that transient analyses offer deeper insights and raise new, interdisciplinary questions for disease research, consequently broadening the applications of dynamical models for outbreak preparedness and management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Dietary plasticity and the importance of salmon to brown bear (Ursus arctos) body size and condition in a low Arctic ecosystem - Lindsey S. Mangipane; Diana J. R. Lafferty; Kyle Joly; Mathew S. Sorum; Matthew D. Cameron; Jerrold L. Belant; Grant V. Hilderbrand; David D. Gustine (Polar Biology, 2020)
Ecological flexibility within animal populations can allow for variation in resource use and foraging decisions. We estimated brown bear ( Ursus arctos ) diet composition in Gates of the Arctic National Park and Preserve, Alaska from 2013 to 2015 to evaluate how variation in foraging behavior influences body condition and size. We used stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope analyses of sectioned brown bear hair samples to evaluate assimilated diet. We then developed a set of a priori linear models to evaluate differences in the diet composition of brown bears ( n = 80) in relation to body fat (%) and mass. The proportion of meat (salmon [ Oncorhynchus keta ] and terrestrial meat combined) in the diet from July through late September varied between male and female bears, with males ( $$\stackrel{-}{x}$$ x - = 62%, SD = 30) assimilating significantly more meat than females ( $$\stackrel{-}{x}$$ x - = 40%, SD = 29). Most of the meat consumed came from marine-derived resources for males (53% of the total diet or 86% of the meat) and females (31% of the total diet or 77% of the meat). As we found the range of observed diets was unrelated to physiological outcomes (i.e., percentage body fat), we suggest that ecological flexibility within populations may provide an adaptive advantage by allowing individuals to reduce competition with conspecifics by foraging on alternate food resources. Identifying variable foraging behaviors within a population can allow for a better understanding of complex behaviors and, ultimately, lead to more informed management decisions related to habitat use, development, and harvest.

Regional-scale environmental resistance to non-native ant invasion - R. J. Warren; M. Candeias; A. Lafferty; L. D. Chick (Biological Invasions, 2020)

Species insurance trumps spatial insurance in stabilizing biomass of a marine macroalgal metacommunity - Thomas Lamy; Shaopeng Wang; Delphine Renard; Kevin D. Lafferty; Daniel C. Reed; Robert J. Miller (Ecology, 2019)
Because natural ecosystems are complex, it is difficult to predict how their variability scales across space and levels of organization. The species‐insurance hypothesis predicts that asynchronous dynamics among species should reduce variability when biomass is aggregated either from local species populations to local multispecies communities, or from metapopulations to metacommunities. Similarly, the spatial‐insurance hypothesis predicts that asynchronous spatial dynamics among either local populations or local communities should stabilize metapopulation biomass and metacommunity biomass, respectively. In combination, both species and spatial insurance reduce variation in metacommunity biomass over time, yet these insurances are rarely considered together in natural systems. We partitioned the extent that species insurance and spatial insurance reduced the annual variation in macroalgal biomass in a southern California kelp forest. We quantified variability and synchrony at two levels of organization (population and community) and two spatial scales (local plots and region) and quantified the strength of species and spatial insurance by comparing observed variability and synchrony in aggregate biomass to null models of independent species or spatial dynamics based on cyclic‐shift permutation. Spatial insurance was weak, presumably because large‐scale oceanographic processes in the study region led to high spatial synchrony at both population‐ and community‐level biomass. Species insurance was stronger due to asynchronous dynamics among the metapopulations of a few common species. In particular, a regional decline in the dominant understory kelp species Pterygophora californica was compensated for by the rise of three subdominant species. These compensatory dynamics were associated with positive values of the Pacific Decadal Oscillation, indicating that differential species tolerances to warmer temperature and nutrient‐poor conditions may underlie species insurance in this system. Our results illustrate how species insurance can stabilize aggregate community properties in natural ecosystems where environmental conditions vary over broad spatial scales.

A strong colonizer rules the trematode guild in an intertidal snail host - Pilar Alda; Nicolás Bonel; Néstor J. Cazzaniga; Sergio R. Martorelli; Kevin D. Lafferty (Ecology, 2019)
We examined the extent to which supply‐side, niche, and competition theories and concepts help explain a trematode community in which one species comprises 87% of the trematode individuals, and the remaining 15 species each have Heleobia australis over four seasons from three distinct habitats from the intertidal area of the Bahía Blanca estuary, Argentina. Inside a snail, trematodes interact with each other with outcomes that depend on facilitation, competition, and preemption, suggesting that dominant species should be common. The abundant trematode species, Microphallus simillimus , is a weak competitor , but has life‐history traits and strategies associated with higher colonization ability that could increase its probability of invading the host first, allowing it to preempt the rare species. Rather than segregate by habitat, trematode species aggregated in pans during the summer where dominant trematode species often excluded subordinate ones. Despite losses to competition, and a lack of niche partitioning, M. simillimus ruled this species‐rich trematode guild through strong recruitment and (potentially) preemption. Therefore, extremely skewed species abundance distributions, like this one, can derive from extremely skewed colonization abilities.

Simultaneous improvement of grain yield and protein content in durum wheat by different phenotypic indices and genomic selection - M. Rapp; V. Lein; F. Lacoudre; J. Lafferty; E. Müller; G. Vida; V. Bozhanova; A. Ibraliu; P. Thorwarth; H. P. Piepho; W. L. Leiser; T. Würschum; et al. (Theoretical and Applied Genetics, 2018)

Dietary plasticity in a nutrient-rich system does not influence brown bear (Ursus arctos) body condition or denning - Lindsey S. Mangipane; Jerrold L. Belant; Diana J. R. Lafferty; David D. Gustine; Tim L. Hiller; Michael E. Colvin; Buck A. Mangipane; Grant V. Hilderbrand (Polar Biology, 2018)

Host density increases parasite recruitment but decreases host risk in a snail–trematode system - J. C. Buck; R. F. Hechinger; A. C. Wood; T. E. Stewart; A. M. Kuris; K. D. Lafferty (Ecology, 2017)
Most species aggregate in local patches. High host density in patches increases contact rate between hosts and parasites, increasing parasite transmission success. At the same time, for environmentally transmitted parasites, high host density can decrease infection risk to individual hosts, because infective stages are divided among all hosts in a patch, leading to safety in numbers. We tested these predictions using the California horn snail, Cerithideopsis californica (= Cerithidea californica ), which is the first intermediate host for at least 19 digenean trematode species in California estuaries. Snails become infected by ingesting trematode eggs or through penetration by free‐swimming miracidia that hatch from trematode eggs deposited with final‐host (bird or mammal) feces. This complex life cycle decouples infective‐stage production from transmission, raising the possibility of an inverse relationship between host density and infection risk at local scales. In a field survey, higher snail density was associated with increased trematode (infected snail) density, but decreased trematode prevalence, consistent with either safety in numbers, parasitic castration, or both. To determine the extent to which safety in numbers drove the negative snail‐density–trematode‐prevalence association, we manipulated uninfected snail density in 83 cages at eight sites within Carpinteria Salt Marsh ( California , USA ). At each site, we quantified snail density and used data on final‐host (bird and raccoon) distributions to control for between‐site variation in infective‐stage supply. After three months, overall trematode infections per cage increased with snail biomass density. For egg‐transmitted trematodes, per‐snail infection risk decreased with snail biomass density in the cage and surrounding area, whereas per‐snail infection risk did not decrease for miracidium‐transmitted trematodes. Furthermore, both trematode recruitment and infection risk increased with infective‐stage input, but this was significant only for miracidium‐transmitted species. A model parameterized with our experimental results and snail densities from 524 field transects estimated that safety in numbers, when combined with patchy host density, halved per capita infection risk in this snail population. We conclude that, depending on transmission mode, host density can enhance parasite recruitment and reduce per capita infection risk.

Mammalian ecophysiology and adaptations to diverse environments - Diana J. R. Lafferty (Ecology, 2017)

The Triple Crown of population biology - Diana J. R. Lafferty (Ecology, 2017)

Moose (Alces alces) hunters subsidize the scavenger community in Alaska - Diana J. R. Lafferty; Zachary G. Loman; Kevin S. White; Anita T. Morzillo; Jerrold L. Belant (Polar Biology, 2016)

Does biodiversity protect humans against infectious disease? Reply - Chelsea L. Wood; Kevin D. Lafferty; Giulio DeLeo; Hillary S. Young; Peter J. Hudson; Armand M. Kuris (Ecology, 2016)

Understanding uncertainty in temperature effects on vector‐borne disease: a Bayesian approach - Leah R. Johnson; Tal Ben-Horin; Kevin D. Lafferty; Amy McNally; Erin Mordecai; Krijn P. Paaijmans; Samraat Pawar; Sadie J. Ryan (Ecology, 2015)
Extrinsic environmental factors influence the distribution and population dynamics of many organisms, including insects that are of concern for human health and agriculture. This is particularly true for vector‐borne infectious diseases like malaria, which is a major source of morbidity and mortality in humans. Understanding the mechanistic links between environment and population processes for these diseases is key to predicting the consequences of climate change on transmission and for developing effective interventions. An important measure of the intensity of disease transmission is the reproductive number R 0 . However, understanding the mechanisms linking R 0 and temperature, an environmental factor driving disease risk, can be challenging because the data available for parameterization are often poor. To address this, we show how a Bayesian approach can help identify critical uncertainties in components of R 0 and how this uncertainty is propagated into the estimate of R 0 . Most notably, we find that different parameters dominate the uncertainty at different temperature regimes: bite rate from 15°C to 25°C; fecundity across all temperatures, but especially ~25–32°C; mortality from 20°C to 30°C; parasite development rate at ~15–16°C and again at ~33–35°C. Focusing empirical studies on these parameters and corresponding temperature ranges would be the most efficient way to improve estimates of R 0 . While we focus on malaria, our methods apply to improving process‐based models more generally, including epidemiological, physiological niche, and species distribution models.

Does biodiversity protect humans against infectious disease? - Chelsea L. Wood; Kevin D. Lafferty; Giulio DeLeo; Hillary S. Young; Peter J. Hudson; Armand M. Kuris (Ecology, 2014)
Control of human infectious disease has been promoted as a valuable ecosystem service arising from the conservation of biodiversity. There are two commonly discussed mechanisms by which biodiversity loss could increase rates of infectious disease in a landscape. First, loss of competitors or predators could facilitate an increase in the abundance of competent reservoir hosts. Second, biodiversity loss could disproportionately affect non‐competent, or less competent reservoir hosts, which would otherwise interfere with pathogen transmission to human populations by, for example, wasting the bites of infected vectors. A negative association between biodiversity and disease risk, sometimes called the “dilution effect hypothesis,” has been supported for a few disease agents, suggests an exciting win–win outcome for the environment and society, and has become a pervasive topic in the disease ecology literature. Case studies have been assembled to argue that the dilution effect is general across disease agents. Less touted are examples in which elevated biodiversity does not affect or increases infectious disease risk for pathogens of public health concern. In order to assess the likely generality of the dilution effect, we review the association between biodiversity and public health across a broad variety of human disease agents. Overall, we hypothesize that conditions for the dilution effect are unlikely to be met for most important diseases of humans. Biodiversity probably has little net effect on most human infectious diseases but, when it does have an effect, observation and basic logic suggest that biodiversity will be more likely to increase than to decrease infectious disease risk.

A multi‐decade time series of kelp forest community structure at the California Channel Islands - David J. Kushner; Andrew Rassweiler; John P. McLaughlin; Kevin D. Lafferty (Ecology, 2013)
Studies of temperate rocky reef communities have added much to our understanding of ecology. However, data on these reef communities can be difficult to obtain; wind, waves, and poor underwater visibility often prevent research diving, and even under the best conditions only a few hours a day can be spent underwater collecting data. Here, we present data on temperate subtidal reef communities at 33 sites, almost half of which the National Park Service has sampled annually since 1982. We present core data sets describing the population dynamics of 16 fish, 37 invertebrate, and 15 algal taxa. We include supplementary data sets documenting the size structure of key species, the relative abundance of all fish, the recruitment of selected invertebrates, and the subtidal water temperature at each site through time. Taken together, these data provide one of the most comprehensive descriptions of nearshore reef community dynamics ever assembled.

Optimal temperature for malaria transmission is dramatically lower than previously predicted - Erin A. Mordecai; Krijn P. Paaijmans; Leah R. Johnson; Christian Balzer; Tal Ben‐Horin; Emily de Moor; Amy McNally; Samraat Pawar; Sadie J. Ryan; Thomas C. Smith; Kevin D. Lafferty (Ecology Letters, 2013)
The ecology of mosquito vectors and malaria parasites affect the incidence, seasonal transmission and geographical range of malaria. Most malaria models to date assume constant or linear responses of mosquito and parasite life‐history traits to temperature, predicting optimal transmission at 31 °C. These models are at odds with field observations of transmission dating back nearly a century. We build a model with more realistic ecological assumptions about the thermal physiology of insects. Our model, which includes empirically derived nonlinear thermal responses, predicts optimal malaria transmission at 25 °C (6 °C lower than previous models). Moreover, the model predicts that transmission decreases dramatically at temperatures > 28 °C, altering predictions about how climate change will affect malaria. A large data set on malaria transmission risk in A frica validates both the 25 °C optimum and the decline above 28 °C. Using these more accurate nonlinear thermal‐response models will aid in understanding the effects of current and future temperature regimes on disease transmission.

More than a meal… integrating non‐feeding interactions into food webs - Sonia Kéfi; Eric L. Berlow; Evie A. Wieters; Sergio A. Navarrete; Owen L. Petchey; Spencer A. Wood; Alice Boit; Lucas N. Joppa; Kevin D. Lafferty; Richard J. Williams; Neo D. Martinez; Bruce A. Menge; et al. (Ecology Letters, 2012)
Ecology Letters (2012) 15 : 291–300 Abstract Organisms eating each other are only one of many types of well documented and important interactions among species. Other such types include habitat modification, predator interference and facilitation. However, ecological network research has been typically limited to either pure food webs or to networks of only a few (

Parasites in food webs: the ultimate missing links - Kevin D. Lafferty; Stefano Allesina; Matias Arim; Cherie J. Briggs; Giulio De Leo; Andrew P. Dobson; Jennifer A. Dunne; Pieter T. J. Johnson; Armand M. Kuris; David J. Marcogliese; Neo D. Martinez; Jane Memmott; et al. (Ecology Letters, 2008)
Parasitism is the most common consumer strategy among organisms, yet only recently has there been a call for the inclusion of infectious disease agents in food webs. The value of this effort hinges on whether parasites affect food‐web properties. Increasing evidence suggests that parasites have the potential to uniquely alter food‐web topology in terms of chain length, connectance and robustness. In addition, parasites might affect food‐web stability, interaction strength and energy flow. Food‐web structure also affects infectious disease dynamics because parasites depend on the ecological networks in which they live. Empirically, incorporating parasites into food webs is straightforward. We may start with existing food webs and add parasites as nodes, or we may try to build food webs around systems for which we already have a good understanding of infectious processes. In the future, perhaps researchers will add parasites while they construct food webs. Less clear is how food‐web theory can accommodate parasites. This is a deep and central problem in theoretical biology and applied mathematics. For instance, is representing parasites with complex life cycles as a single node equivalent to representing other species with ontogenetic niche shifts as a single node? Can parasitism fit into fundamental frameworks such as the niche model? Can we integrate infectious disease models into the emerging field of dynamic food‐web modelling? Future progress will benefit from interdisciplinary collaborations between ecologists and infectious disease biologists.

Can parasites be indicators of free-living diversity? Relationships between species richness and the abundance of larval trematodes and of local benthos and fishes - Ryan F. Hechinger; Kevin D. Lafferty; Todd C. Huspeni; Andrew J. Brooks; Armand M. Kuris (Oecologia, 2007)

Keeping the herds healthy and alert: implications of predator control for infectious disease - Craig Packer; Robert D. Holt; Peter J. Hudson; Kevin D. Lafferty; Andrew P. Dobson (Ecology Letters, 2003)
Predator control programmes are generally implemented in an attempt to increase prey population sizes. However, predator removal could prove harmful to prey populations that are regulated primarily by parasitic infections rather than by predation. We develop models for microparasitic and macroparasitic infection that specify the conditions where predator removal will (a) increase the incidence of parasitic infection, (b) reduce the number of healthy individuals in the prey population and (c) decrease the overall size of the prey population. In general, predator removal is more likely to be harmful when the parasite is highly virulent, macroparasites are highly aggregated in their prey, hosts are long‐lived and the predators select infected prey.

Conflict of interest between a nematode and a trematode in an amphipod host: test of the "sabotage" hypothesis - Fré dé ric Thomas; Jé rô me Fauchier; Kevin Lafferty (Behavioral Ecology and Sociobiology, 2002)